Impacts of Biofuel Policies on Welfare and Food Security: Assessing the Socioeconomic and Environmental Trade-offs in Sub-Saharan Africa - Kiggundu, Nicholas; Arhin, Samuel Gyebi; Banadda, Noble; Kabenge, Isa (International Journal of Renewable Energy Research, 2017)
The global interest in biofuels production is agued to have substantial impacts on food security. A slew of studies have identified a nexus between biofuel production intensification and food price hikes in the international market. Regardless of the results of these studies, global biofuels production keeps increasing and it is projected to escalate even further within the next decade. A major concern is that some sub-Saharan African countries with food security worries have policies to enhance the production and use of first generation biofuels. In view of that, this paper examines the potential consequences of diverting food and agricultural lands for biofuels production with a focus on sub-Saharan Africa. It reviews the current and projected trends in the production of biofuels and trade of feedstocks, analyses the potential of “food gap”, land use change and associated carbon emissions and the effects on biodiversity and water resources within the region. In conclusion, the study accentuates the doubt on the potential of first generation biofuels as a realistic source of energy particularly in sub-Saharan Africa as it could have substantial effects on the regions’ food security as well as on its natural resource. It also suggests ways to enhance the sustainability of the region’s biofuel policies to maximize welfare gains and enhance food security.
Keywords: Biofuels, food security, land use change, policies, sub-Saharan Africa.